تطبيق تعليم اللغة القائم على المهام من خلال كتابة المعجم الموضوعي لإتقان المفردات لدى طلاب المدرسة الثانوية الحكومية ١٦ جاكرتا - Maulana, Tengku; Nawawi, Mukhshon (Al-Muyassar: Journal of Arabic Education, 2025)
This study aims to discuss the emphasis of the 2013 curriculum on improving higher-order thinking skills (HOTS), by highlighting the lack of appropriate assessment instruments to develop these skills in students. Its novelty lies in the development of Arabic language test questions designed explicitly for fifth-grade students at the Darul Hikmah Integrated Islamic Elementary School in Bekasi, which integrates HOTS principles to align with modern pedagogical goals. Using the 4D development model (define, design, develop, disseminate), this study uses a rigorous methodology, including theoretical validation, empirical validation, reliability testing, and item analysis. Theoretical validation was carried out by experts using a Likert scale questionnaire, while empirical validation used point biserial correlation. Reliability was assessed using the KR20 formula, and the level of difficulty was analyzed through the difficulty index. Involving 20 students, the findings revealed: 1) The instrument's feasibility score was 91.5%, considered very valid. 2) Five items were valid based on biserial correlation. 3) Moderate reliability (0.59). 4) The average difficulty index was 0.52, reflecting high-quality questions. This study offers an innovative approach to Arabic language assessment, which paves the way for increased integration of HOTS in primary education.